A systematic review of interventions for preventing tobacco sales to minors. - Stead, L; Lancaster, T (2000)
OBJECTIVE: To assess the effectiveness of interventions to reduce underage access to tobacco by deterring shopkeepers from making illegal sales. METHOD: Systematic literature review. DATA SOURCES: The Cochrane Tobacco Addiction group specialised register and Medline. Studies of interventions to alter retailer behaviour were identified. The terms used for searching combined terms for smoking and tobacco use with terms for minors, children or young people, and retailers, sales or commerce. STUDY SELECTION: Studies in which there was an intervention with retailers of tobacco, either through education about, or enforcement of, local ordinances. The outcomes were changes in retailer compliance with legislation (assessed by test purchasing), changes in young people's perceived ease of access to tobacco products, and changes in smoking behaviour. Controlled studies with or without random allocation of retail outlets or communities, and uncontrolled studies with pre- and post intervention assessment, were included. DATA EXTRACTION: Two reviewers assessed studies for inclusion. One extracted data with checking by the second. DATA SYNTHESIS: The results were synthesised qualitatively, with greater weight given to controlled studies. Thirteen of 27 included studies used controls. RESULTS: Giving retailers information was less effective in reducing illegal sales than active enforcement and/or multicomponent educational strategies. No strategy achieved complete, sustained compliance. In three controlled trials, there was little effect of intervention on youth perceptions of access or prevalence of smoking. CONCLUSIONS: Interventions with retailers can lead to large decreases in the number of outlets selling tobacco to youths. However, few of the communities studied in this review achieved sustained levels of high compliance. This may explain why there is limited evidence for an effect of intervention on youth perception of ease of access to tobacco, and on smoking behaviour.